Opportunity versus Necessity : Understanding the Heterogeneity of Female Micro-Entrepreneurs - Calderon, Gabriela; Iacovone, Leonardo; Juarez, Laura (Published by Oxford University Press on behalf of the World Bank, 2019)
Entrepreneurs that voluntarily choose to start a business because they are able to identify a good business opportunity and act on it opportunity entrepreneurs might be different along various dimensions from those who are forced to become entrepreneurs because of lack of other alternatives necessity entrepreneurs. To provide evidence on these differences, this article exploits a unique data set covering a wide array of characteristics, including cognitive skills, noncognitive skills, and managerial practices, for a large sample of female entrepreneurs in Mexico. Descriptive results show that on average opportunity entrepreneurs have better performance and higher skills than necessity entrepreneurs. A discriminant analysis reveals that discrimination is difficult to achieve based on these observables, which suggests the existence of unobservables driving both the decision to become an opportunity entrepreneur and performance. Thus, an instrumental variables estimation is conducted, using state economic growth in the year the business was set up as an instrument for opportunity, to confirm that opportunity entrepreneurs have higher performance and better management practices.